Rare bird sighting for Prairie Falcon at DeSoto National Wildlife Refuge in 1980 - Padelford, Babset al; Padelford, Lorenet al (1980)
Rare bird sighting for a Prairie Falcon at DeSoto National Wildlife Refuge in Harrison County, IA on November 15, 1980 with additional species sighting information. Epson - sheet feed